The scientific Culture's Level Among Early Childhood Department Female Students at Umm Al-Qura University in the Light of Some Variables - Ebtehal Ghandourah (Umm Al-Qura University, 2022)
The study aimed to reveal the scientific culture's level among the early childhood department female students at Umm Al-Qura University, to reveal the statistically significant differences in the scientific culture's level , attributed to: type of secondary school (Public/private), track (Scientific/Literary), student GPA. To achieve the study objectives, the descriptive (analytical) approach was adopted; A multiple choice test was prepared to measure the scientific culture's level , after verifying the tools validity and reliability, it was applied to the study sample (88) fourth-level female students. Findings of the study: The scientific culture's level among the study sample was (Moderate), with relatively importance (66.6%). There are no statistically significant differences at the level of significance (α≤0.05) in the scientific culture's level according to the variable (specialization), (school), there are also no statistically significant differences in the of Scientific culture's level according to the variable (GPA) in (the concept of science, its objectives and results, the methods and processes of science); There are statistically significant differences at the level of significance (α ≤ 0.05) in the level of scientific culture according to the variable (GPA) in the two dimensions (science ethics, scientific knowledge) and the total test; The significance level for these two dimensions and the overall test is less than (0.05).